2018
DOI: 10.1007/s00216-018-1059-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic study of human tissue and urine in clear cell renal carcinoma by LC-HRMS and PLS-DA

Abstract: Renal cell carcinoma (RCC) is the most prevalent and lethal malignancy of the kidney. Despite all the efforts made, no tissue biomarker is currently used in the clinical management of patients with kidney cancer. A search for possible biomarkers in urine for clear cell renal cell carcinoma (ccRCC) has been conducted. Non-targeted metabolomic analyses were performed on paired samples of surgically removed renal cancer and normal tissue, as well as on urine samples. Extracts were analyzed by liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Significantly higher urinary carnitine was detected in chromophobes and ccRCC relative to oncocytomas. This finding is particularly interesting as elevated levels of carnitine and its derivatives have been previously reported in the urine of RCC patients and confirmed in xenograft models and RCC cell lines [9,24]. These authors, however, did not define the histological class of the samples involved but revealed a stage-dependent increase of urinary carnitine and acylcarnitines in RCC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Significantly higher urinary carnitine was detected in chromophobes and ccRCC relative to oncocytomas. This finding is particularly interesting as elevated levels of carnitine and its derivatives have been previously reported in the urine of RCC patients and confirmed in xenograft models and RCC cell lines [9,24]. These authors, however, did not define the histological class of the samples involved but revealed a stage-dependent increase of urinary carnitine and acylcarnitines in RCC.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we have detected increased o-acetylcarnitine in all RCC stages relative to benign samples (Table 2). Carnitine and acylcarnitines are essential intermediates for the transfer of long chain fatty acids to the mitochondria for β-oxidation and an accumulation in the cell may imply an increased demand as a result of rapid fatty acid oxidation to meet higher tumoral energy requirements [24]. Conversely, Wettersten et al, found that the accumulation of acylcarnitine did not overlap with upregulation of fatty acid oxidation enzymes in RCC [25].…”
Section: Discussionmentioning
confidence: 99%
“…They include a number of metabolites of host or bacterial origin including allantoin, and cis-4-decenedioic acid, decanoylcarnitine, and dodecanedioylcarnitine, respectively. These metabolites and compounds are indicative of urea metabolism 42 and fatty acid oxidation defects associated with disease, 43 which may be relevant for IBS pathology. However, as noted, the strongest features that separate the IBS urine metabolome (Supplementary Table 15) are associated with the metabolism of dietary or medication components (nodes E5 and E7).…”
Section: Integrative Analysis Of Diet Microbiome and Metabolome Revmentioning
confidence: 99%
“…In the last decade, untargeted metabolomic profiling, using liquid chromatography combined with mass spectrometry (LC-MS), has proven to be a promising tool in kidney cancer diagnostics and research. Previous MS-based metabolomic studies have already shown the possibility of discriminate RCC patients from healthy controls using tissue 1419 , urine 17,2022 or serum 23 . Moreover, a recent study has also demonstrated the possibility of discrimination of different RCC stages, from 1 to 4, using combined metabolomic studies 24 .…”
Section: Introductionmentioning
confidence: 99%